Ecuador in the global instability - K. M. Bonilla; I. V. Lazanyuk; D. C. Regalado (Путеводитель предпринимателя, 2020)
The article is devoted to the study of state measures taken in the context of global instability in the Republic ofEcuador in order to confront historical problems and the consequences of the global crisis. Based on the analysis of macroeconomic indicators, was demonstrated the extent of the country’s involvement in the global financial crisis. The article analyzes the main directions and results of government measures, the main purpose of which is to change the production matrix to achieve a high level ofquality of life for the population. The results of the study confirm the legitimacy of the efforts of the Government ofEcuador to stabilize all sectors of the economy through planning. In addition, the results of the study indicate the need for taking certain measures to eliminate risks and instability in the consequences of exogenous and endogenous factors.